Spinoza’s Critique of Descartes’ Dualism and The Relevance of Both In The Digital Age - Hasibuan, Damri (Communica : Journal of Communication, 2025)
The digital era presents complex philosophical and ethical challenges, prompting an evaluation of traditional frameworks like mind-body dualism for new ethical foundations. This paper critically examines Baruch Spinoza’s critique of René Descartes’ dualism and their contemporary relevance in addressing the ethical and existential challenges of the digital age. Employing library research and a critical-philosophical approach, this study analyzes primary and secondary texts. This research finds that while Descartes’ rationalism laid the groundwork for modern scientific epistemology, its inherent dualism contributes to digital ethical and existential crises. Conversely, Spinoza’s monistic ethics of unity and natural order offer an alternative framework for navigating the moral dilemmas of a digital society. The study concludes by emphasizing the importance of synthesizing individual and relational rationality as a strong ethical foundation for human progress amidst rapid technological advancement.